Management of Radiation Safety at Curtin University - an Overview - Siddiqui, Salim (AINSE, 2012)
Occupational health and safety in a workplace plays a vital role in the smooth running of any institution in terms of regulatory compliance and the well being of its people. The tasks become even more demanding for big institutions such as Curtin University, which deals with a large number of people including staff, students, visitors and contractors working in diverse working conditions. In order to make the existing system more efficient, Curtin University has recently restructured its Health and Safety management system, in which the role of each safety and health advisor, their hierarchical position, the line of accountability and the reporting system is clearly mapped out. The main focus of the new structure is strengthening training and induction programs reinforcing regulatory awareness, defining responsibilities and obligation, analysis and risk assessment and online incident reporting system. The radiation safety is an integral part of the new health and safety management structure. This presentation highlights the hierarchical position of the radiation safety officer in the new structure, the role of the radiation safety committee, the management of radiation safety across the university and responsibilities of the radiation safety officer under the Radiation Safety Regulations.